Measuring NAD+ levels in mouse blood and tissue samples via a surrogate matrix approach using LC–MS/MS. (June 2014) - Liang, Xiaorong; Yang, Lulu; Qin, Ann R; Ly, Justin; Liederer, Bianca M; Messick, Kirsten; Ma, Shuguang; Zak, Mark; Dragovich, Peter S; Dean, Brian J; Hop, Cornelis ECA; Deng, Yuzhong
Background: NAD + is an endogenous analyte and is unstable during blood sample collection, both of which present obstacles for quantitation. Moreover, current procedures for NAD + sample collection require onsite treatment with strong acid to stabilize the NAD + in mouse blood cells.Results: NAD + can be stabilized by addition of acid before the frozen mouse blood sample was thawed. A simple sample collection procedure was proposed to facilitate the analysis of NAD + in mouse blood and tissue samples. A LC–MS/MS method was developed for quantifying NAD + in mouse blood and various tissue samples. The described method was used to measure endogenous NAD + levels in mouse blood following oral administration of the nicotinamide phosphoribosyltransferase inhibitor GNE-617.Conclusion: This study presents a suitable assay and sample collection procedure for high throughput screening of NAD + samples in preclinical discovery studies.